2013
DOI: 10.1371/journal.pone.0073674
|View full text |Cite
|
Sign up to set email alerts
|

SNP Discovery by Illumina-Based Transcriptome Sequencing of the Olive and the Genetic Characterization of Turkish Olive Genotypes Revealed by AFLP, SSR and SNP Markers

Abstract: BackgroundThe olive tree (Olea europaea L.) is a diploid (2n = 2x = 46) outcrossing species mainly grown in the Mediterranean area, where it is the most important oil-producing crop. Because of its economic, cultural and ecological importance, various DNA markers have been used in the olive to characterize and elucidate homonyms, synonyms and unknown accessions. However, a comprehensive characterization and a full sequence of its transcriptome are unavailable, leading to the importance of an efficient large-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 103 publications
1
57
0
Order By: Relevance
“…Combining complex trait analysis with transcriptome analysis is an important step in molecular genetic studies (Li et al, 2005). Transcriptome SNPs are associated with genes or functional regions of the genome (Xu et al, 2012;Kaya et al, 2013), which is why a number of researchers have focused on combining high-throughput transcriptome data and quantitative trait loci (QTL) detection to understand biological pathways related to complex traits (Mootha et al, 2003;Kirst et al, 2004;Schadt et al, 2005). This new approach is referred to as 'genetical genomics' or 'integrative genomics' and involves the use of gene and genetic marker expression levels to define genomic regions referred to as expression quantitative trait loci (eQTL) (Mignon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Combining complex trait analysis with transcriptome analysis is an important step in molecular genetic studies (Li et al, 2005). Transcriptome SNPs are associated with genes or functional regions of the genome (Xu et al, 2012;Kaya et al, 2013), which is why a number of researchers have focused on combining high-throughput transcriptome data and quantitative trait loci (QTL) detection to understand biological pathways related to complex traits (Mootha et al, 2003;Kirst et al, 2004;Schadt et al, 2005). This new approach is referred to as 'genetical genomics' or 'integrative genomics' and involves the use of gene and genetic marker expression levels to define genomic regions referred to as expression quantitative trait loci (eQTL) (Mignon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 6 genotypes were examined to discover SSRs in lentil and 1.38 × 10 6 reads were generated (Kaur et al, 2011). In olive, Kaya et al (2013) performed transcriptome sequencing of cDNA from 5 distinct olive genotypes. The resulting 126,542,413 sequencing reads in this study were assembled into 22,052 contigs and identified 2987 SNP markers.…”
Section: Sequence Assembly and Snp Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Olive has been considered to be one of the most diverse tree species with about 1200 olive cultivars grown worldwide (Bartolini et al, 1998). The characterization of olive germplasm has been mainly carried out by using morphological and agronomic characters (Cantini et al, 1999), but most of them used for the characterization of olive genotypes can be affected by environmental factors which could lead to misidentification and incorrect naming of olive genotypes (Ipek et al, 2012;Kaya et al, 2013). Therefore, DNA molecular markers, which only reflect nucleotide diversity in the genome of genotypes, have been utilized to estimate genetic relationships between olive genotypes and cultivars in most of the recent genetic diversity studies (reviewed by Bracci et al, 2011).…”
Section: Introductionmentioning
confidence: 99%